Genomic medicine, precision medicine, and personalized medicine: A survey of Turkish physicians' perspectives on new paradigms in medicine - Zerri̇n Gamsizkan; Mehmet Ali̇ Sungur (Medicine Science)
Advances in medicine and new approaches are transforming health services. How these new approaches affect clinicians' decision-making is still unclear. This research aimed to evaluate the reflections of the concepts of personalized, genomic and precision medicine, which are new approaches in medicine, among physicians, and to discuss these practices together with their theoretical, practical and moral dimensions. In this study, a questionnaire was used to question the theoretical, practical utility and necessity, and moral perspectives of clinicians about the applications of genomic medicine, precision medicine, and personalized medicine. The questionnaire also questioned the clinical decision-making processes of these clinicians. In the study, 58.7 (n=186) of the physicians participating in the study thought that planning treatment according to genetic medicine would solve many problems and that the medicine of the future would advance in this direction. In the study, 49.5% (n=157) of the physicians participating in the study stated that there is no objection to genomic and precision medicine applications. It has been stated that 39.1% (n=124) of the physicians have concerns that a new area of exploitation may occur in the medical profession. On the other hand, 20.1% (n= 64) of the physicians stated that such practices would distract the medical profession from evidence-based practices. On the other hand, 68.5% (n=217) of the physicians stated that they wanted to receive training on personalized, genomic and precision medicine. The results of the study show that although clinicians think that genomic and precision medicine applications are the medicine of the future, the majority of them have reservations. Before these applications become widespread in all medical fields, their theoretical, practical and moral frameworks should be established. [Med-Science 2025; 14(1.000): 38-42]